2019
DOI: 10.1002/ece3.4813
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict in action: An antagonistic relationship between maternal and paternal sex allocation in the tammar wallaby, Notamacropus eugenii

Abstract: Sex ratio biases are often inconsistent, both among and within species and populations. While some of these inconsistencies may be due to experimental design, much of the variation remains inexplicable. Recent research suggests that an exclusive focus on mothers may account for some of the inconsistency, with an increasing number of studies showing variation in sperm sex ratios and seminal fluids. Using fluorescent in‐situ hybridization, we show a significant population‐level Y‐chromosome bias in the spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Studies on disparate mammal species, including the Pygmy Hippopotamus (Choeropsis liberiensis; Saragusty et al 2012), the Whitefooted Deermouse (Peromyscus leucopus; Malo et al 2017), and another Australian marsupial, the Tammar Wallaby (Notamacropus eugenii; Edwards et al 2019), have implicated fathers to be arbiters of sex allocation by reporting positive correlations between sperm (i.e., proportion of X-to y-CBS) and offspring sex ratios. Specifically, the tammar wallaby study reported a population-level bias in both the production of y-CBS and the birth of sons (Edwards et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on disparate mammal species, including the Pygmy Hippopotamus (Choeropsis liberiensis; Saragusty et al 2012), the Whitefooted Deermouse (Peromyscus leucopus; Malo et al 2017), and another Australian marsupial, the Tammar Wallaby (Notamacropus eugenii; Edwards et al 2019), have implicated fathers to be arbiters of sex allocation by reporting positive correlations between sperm (i.e., proportion of X-to y-CBS) and offspring sex ratios. Specifically, the tammar wallaby study reported a population-level bias in both the production of y-CBS and the birth of sons (Edwards et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm SRs can also differ between males. [29,30,32] Although variance in a trait is a prerequisite for selection, a fair amount of the interindividual variation in sperm SR may be caused by random processes that do not contribute to selection. Three studies have played a major role in elucidating the drivers of this variation.…”
Section: Individual Differences Are Particularly Instructive From An mentioning
confidence: 99%
“…Some authors have suggested that a population-level comparison of sperm SR and SR at birth (or inde-pendence) allows sexual conflicts between fathers and mothers over offspring SRs to be examined. Thus, Edwards et al [30] showed a population-level sperm SR biased towards Y-CBS (51.1%) but a weaning SR that is female-biased (80%) in an article entitled "Sexual conflict in action: an antagonistic relationship between maternal and paternal sex allocation in the tammar wallaby". Unfortunately, these conclusions are questionable for two reasons.…”
Section: Strengths and Limitations Of Existing Studiesmentioning
confidence: 99%
See 2 more Smart Citations